Perencanaan Tebal Perkerasan Lentur Ruas Jalan Teluk Bayur-Kota Padang Sta 0+000-5+000 - Fitra Rifwan; Oktaviani Oktaviani; Nadra Mutiara Sari; Yuni Kurniati (Jurnal Pembangunan Nagari, 2018)
The Padang city is going to change the land use because of a transportation development. The increasing number of vehicle that occure every years in this city make a problem related to the capacity of the transportation infrastructure, such as the road. The road of Teluk Bayur - Padang is its location which is the area of case study. The municipal and provincial authority are working together to solve the problem with conducting the road improvement project. It is worked by using 2 road types, such as rigid and flexible pavement. The different types become a little question why they are not the same in equal traffic load based on LHR data. According to the conditions, an alternative design needs to be made. The design is not different with existing traffic load conditions and has durability for 10 years. The design is flexible pavement analyzed by using the guideline ‘Petunjuk Perencanaan Tebal Perkerasan Lentur Jalan Raya dengan Metode Analisa Komponen (MAK)’ , 1987 made by Ministry of Public Works of Indonesia. The results produced each layer's thickness of the road, such as D1 = surface = 8 cm, D2 = subbase = 24 cm, and base = 10 cm.